Prenatal evaluation in primary care in Northeast Brazil: factors associated with its adequacy - Esther Pereira da Silva; Antônio Flaudiano Bem Leite; Roberto Teixeira Lima; Mônica Maria Osório (Universidade de São Paulo, 2019)
ABSTRACT OBJECTIVE To characterize prenatal care and verify possible factors associated with its adequacy. METHODS This is a cross-sectional study based on interviews with health care professionals and consultations on official documents of women attending prenatal of the primary health care in the city of João Pessoa, capital of Paraíba, in the Northeast region of Brazil. Prenatal care was evaluated by an index with criteria referring to aspects of structure, process and outcome, denominated IPR/Prenatal. The multivariate logistic regression method revealed that demographic, socioeconomic, reproductive and maternal morbidity variables were possible determinants for prenatal adequacy. RESULTS The survey involved 130 services and 1,625 primary health care patients. Prenatal care was adequate in approximately 23% of the cases. Low prevalence of referral to maternity, educational strategies and examinations were observed. The analysis showed that non-adolescent women (OR = 1,390), with a longer period of schooling (OR = 1.750), higher per capita income (OR = 1,870) and primiparous women (OR = 1,230) were more likely to have an adequate prenatal. CONCLUSIONS Prenatal care, when evaluated by broader criteria, showed a low percentage of adequacy. Strategies should be developed to ensure the referral to the maternity where the birth will take place and health education activities and examinations to provide adequate prenatal care in the municipality under study. In addition, factors associated with adequacy must be considered by managers and health professionals.